Process quality analysis of products - Chen, KS; Chen, SC; Li, RK (My University, 2002)
Process capability indices are widely regarded as a flexible means of evaluating the quality and performance of a process. Accreditation by the Quality System Requirement QS9000 requires an agent to conduct a global evaluation on the process capability over the entire product family from a plant. Generally, the process capability of the whole product family is an important reference for evaluation when producing a new product or designing a new process. Therefore developing a scheme to evaluate the process capability of the whole product family or series is crucial for industry This paper takes the production of capacitors as an example of a new method for evaluating the process capability of a whole product family. As the quality characteristic for producing capacitors is "the smaller the better", the upper specification limits of the capacitors of various specifications should first be established. The process capability index C-pu for products for which "smaller is better" is then used as an evaluation toot to calculate the process capability indices for individual specified products. The relationship between the process capability indices and the yield will be studied. A process capability index is proposed to reflect the global yield of the whole product family and to serve as a reference for evaluating process capability for designing new processes or developing new products. The process capabilities for all products can thus be evaluated and the performance of each process can be evaluated according to the colour management method. Managers can determine easily whether products meet their specifications and take action to improve them if necessary, according to the colour management method.
Keywords: colour management method; process capability indices; product family; upper specification limit; yield